Law and the production of precarious work in Europe: an introduction. Issue 3 (September 2022) - Bogoeski, Vladimir; Costamagna, Francesco
Abstract: The introductory article sets out the background and the content of the Symposium on 'Law and the Production of Precarious Work in Europe'. The analysis builds on the premise that European (EU) law, together with international and national law, is constitutive of precarious forms of work and work relations in different national and local contexts. The Symposium takes issue with the specific legal frameworks and regimes that are related to structuring various forms of precarious and exploitable labour, by exploring how (EU) law orders the world of work through legal regimes and regulatory frameworks governing specific forms of labour mobility across borders, as well as by looking at the other components of the structures and institutional interactions underlying the broader political economy where precarious forms of work materialise.